You ≠ me: individual differences in the structure of social cognition - Shaw, D J; Czekóová, K; Pennington, C R; Qureshi, A W; Špiláková, B; Salazar, M; Brázdil, M; Urbánek, T (Psychological research, 2020)
This study investigated the structure of social cognition, and how it is influenced by personality; specifically, how various socio-cognitive capabilities, and the pattern of inter-relationships and co-dependencies among them differ between divergent personality styles. To measure social cognition, a large non-clinical sample (n = 290) undertook an extensive battery of self-report and performance-based measures of visual perspective taking, imitative tendencies, affective empathy, interoceptive accuracy, emotion regulation, and state affectivity. These same individuals then completed the Personality Styles and Disorders Inventory. Latent Profile Analysis revealed two dissociable personality profiles that exhibited contrasting cognitive and affective dispositions, and multivariate analyses indicated further that these profiles differed on measures of social cognition; individuals characterised by a flexible and adaptive personality profile expressed higher action orientation (emotion regulation) compared to those showing more inflexible tendencies, along with better visual perspective taking, superior interoceptive accuracy, less imitative tendencies, and lower personal distress and negativity. These characteristics point towards more efficient self-other distinction, and to higher cognitive control more generally. Moreover, low-level cognitive mechanisms served to mediate other higher level socio-emotional capabilities. Together, these findings elucidate the cognitive and affective underpinnings of individual differences in social behaviour, providing a data-driven model that should guide future research in this area.
Keywords: kognice; Empathy; osobnost; individualita; sociální percepce; Social Perception; sociální chování; Individuality; lidé; emoce; Female; Male; ženské pohlaví; Cognition; Personality; mladý dospělý; Humans; mužské pohlaví; Young Adult; empatie; Social Behavior; Emotions